The Construction of Power Relations in Last Night in Soho - Nafisah, Nia; Aulia, Siti Fajriyah Nida (Humanus, 2025)
One of a film’s characteristics is raising awareness about a particular social phenomenon. In Last Night in Soho, Director Edgar Wright (2021) constructed a phenomenon of power relations from the perspective of an aspiring singer in the 1960s. The present study aims to reveal how power relations among the main characters in Last Night in Soho are constructed. Employing a qualitative approach with textual analysis and film theory from Bordwell and Thompson (2012) and within the theoretical framework of Foucault’s (1975/2019) power relations and Noggle’s (1996) manipulation, the study found that the power relations between the main characters, Sandie and Jack, who are involved in a romantic relationship, are manifested through several power instruments, namely: manipulation, domination, and resistance. These power relations affect the physical and psychological aspects of the subject of power, even having a traumatic effect. Thus, the study reinforces Foucault’s premise that power is everywhere and circulated in any discourse, including romantic discourse. Furthermore, the study highlights the vulnerability of aspiring artists and shows how ‘authoritative’ individuals in the entertainment industry can manipulate artists’ dreams and ambitions.  By manipulating a romantic relationship, they exploit the artists' naïve determination and coerce them to engage in lowly activities under the guise of career advancement.